The Relationship Between the Principal’s Supervision and Work Climate with the School’s Organizational Performance - Fitriah, Fitriah (PPSDP International Journal of Education, 2023)
The goal of this study is to examine how the supervision and workplace culture of the principal affect the effectiveness of school organizations. Quantitative correlational methods are used in the study methodology. 120 instructors from the 4 public high schools in the Kayuagung District made up the research sample, which was chosen at random. According to the study’s findings, work environment and organizational performance at schools are strongly correlated with the supervision of school principals. By planning, carrying out, and assessing educational activities at these institutions, school principals can improve the performance of school organizations. The performance of school organizations might also alter depending on the climate of the school. Performance can be impacted by a positive school environment. The findings of this study have ramifications for initiatives aimed at enhancing school organizational performance through elements like work environment and principal supervisory effectiveness.